(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article is addressed to students covering the topic of ‘first degree Diophantine equations & their solutions’. In the article the main focus is on Diophantine equation solutions via geometric interpretation. The concern for Diophantine equations is clearly bound to human nature – its traces are found in preserved documents over thousands of years. Diophantine equations also give opportunity to solve algebraic problems using integers.